Walking on thin ice! Identifying methamphetamine "drug mules" on digital plain radiography - Abdul Rashid, Saiful Nizam; Mohamad Saini, Suraini; Abdul Hamid, Suzana; Muhammad, Sharifah Siti Jusna; Mahmud, Rozi; Thali, Michael J.; Flach, Patricia Mildred (British Institute of Radiology, 2014)
Objective: The purpose of this study was to retrospectively evaluate the sensitivity, specificity and accuracy of identifying methamphetamine (MA) internal payloads in “drug mules” by plain abdominal digital radiography (DR). Methods: The study consisted of 35 individuals suspected of internal MA drug containers. A total of 59 supine digital radiographs were collected. An overall calculation regarding the diagnostic accuracy for all “drug mules” and a specific evaluation concerning the radiological appearance of drug packs as well as the rate of clearance and complications in correlation with the reader's experience were performed. The gold standard was the presence of secured drug packs in the faeces. Results: There were 16 true-positive “drug mules” identified. DR of all drug carriers for Group 1 (forensic imaging experienced readers, n = 2) exhibited a sensitivity of 100%, a mean specificity of 76.3%, positive predictive value (PPV) of 78.5%, negative predictive value (NPV) of 100% and a mean accuracy 87.2%. Group 2 (inexperienced readers, n = 3) showed a lower sensitivity (93.7%), a mean specificity of 86%, a PPV of 86.5%, an NPV of 94.1% and a mean accuracy of 89.5%. The interrater agreement within Group 1 was 0.72 and within Group 2 averaged to 0.79, indicating a fair to very good agreement. Conclusion: DR is a valuable screening tool in cases of MA body packers with huge internal payloads being associated with a high diagnostic insecurity. Diagnostic insecurity on plain films may be overcome by low-dose CT as a cross-sectional imaging modality and addressed by improved radiological education in reporting drug carriers on imaging. Advances in knowledge: Diagnostic signs (double-condom and halo signs) on digital plain radiography are specific in MA “drug mules”, although DR is associated with high diagnostic insecurity and underreports the total internal payload.